Do Children With Autism Spectrum Disorders Understand Pantomimic Events? - Adornetti, Ines; Ferretti, Francesco; Chiera, Alessandra; Wacewicz, Slawomir; Żywiczyński, Przemysław; Deriu, Valentina; Marini, Andrea; Magni, Rita; Casula, Laura; Vicari, Stefano; Valeri, Giovanni (Frontiers in Psychology, 2019)
Impairments of motor representation of actions have been reported as a core component of Autism Spectrum Disorders (ASD). Individuals with ASD have difficulties in a number of functions such as assuming anticipatory postures, imitating body movements, producing and understanding gestures, and recognizing motor intentions. Such cognitive-motor abilities are all involved in pantomime. However, the available evidence on the production and comprehension of pantomime in individuals with ASD is still inconclusive. The current investigation assessed pantomime comprehension in forty children with high functioning ASD and forty children with typical development balanced for age, IQ, and cognitive profile. The participants were asked to watch video-recordings of pantomimes representing simple transitive events enacted by actors and match them to the corresponding pictorial representations. Such pantomimes were delivered in two conditions with different levels of information content (i.e., lean or rich). The two groups of children performed similarly on these tasks. Nonetheless, children with ASD who were administered the pantomimes in the lean condition performed worse than participants who were administered the informatively richer pantomimes. The methodological implications for interpretation of previous findings and future studies are discussed.